2019
DOI: 10.3389/fpsyt.2019.00616
|View full text |Cite
|
Sign up to set email alerts
|

Altered Interoceptive Processing in Generalized Anxiety Disorder—A Heartbeat-Evoked Potential Research

Abstract: Generalized anxiety disorder (GAD) is one of the most common anxiety disorders. The brain’s dysfunctional processing of interoceptive information is increasingly recognized as an important component of anxiety disorders. However, the neural mechanisms remain insufficiently understood. In the present study, patients with GAD and healthy control participants underwent an eyes-closed (EC) resting state (interoception) and eyes-open (EO) resting state (exteroception) without paying conscious attention to heartbeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 74 publications
4
37
0
Order By: Relevance
“…Aside from differences in diagnostic features, it is also plausible to assume that divergent task instructions during HEP measurement played a role. In particular, HEP amplitudes seem to be larger under resting EEG conditions with eyes closed, compared to open eyes, which is intuitively understandable, as interoception can be sharpened by precluding input from other sensory systems [32,50,56,60].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Aside from differences in diagnostic features, it is also plausible to assume that divergent task instructions during HEP measurement played a role. In particular, HEP amplitudes seem to be larger under resting EEG conditions with eyes closed, compared to open eyes, which is intuitively understandable, as interoception can be sharpened by precluding input from other sensory systems [32,50,56,60].…”
Section: Discussionmentioning
confidence: 84%
“…Consistent with these theoretical considerations, altered HEPs have been found in psychopathological disorders that are clinically characterized by reduced capacity for interoception and poor awareness of own feelings. For instance, smaller HEP amplitudes have been observed in depression compared to controls [30], whereas increased amplitudes have been reported in social anxiety disorder [31,32]. To date, only a few studies have investigated interoception in BPD.…”
Section: Introductionmentioning
confidence: 99%
“…The volume in the MPFC was seen to be related to heartbeat sensitivity in patients with GAD but not in the healthy population. 25 There are few studies that have examined the relationship between structural MRI and cardiac perception in the healthy population. To our knowledge, it should be the first study to explore the neural structures involved in processing enhanced cardiac perception in patients with GAD.…”
Section: Main Findingsmentioning
confidence: 99%
“…Previous research reported that the assessment of heartbeat perception in a solely behavioural or selfreporting questionnaire-based manner is not ideal, and indicated that heartbeat-evoked brain potentials (HEP), an electrocortical potential time locked to the cardiac R wave, might be a more objective quantitative assessment tool. 25 It was proposed to use HEP to evaluate heartbeat perception in future studies. Further limitations are that some patients with GAD received different treatments, which is a well-recognised issue in similar brain structure studies.…”
Section: Limitationsmentioning
confidence: 99%
“…Another important, and to a degree unexpected, finding within this study of non-clinical individuals was the absence of a relationship between trait anxiety and the timing of heartbeat sensations. Indeed, disrupted interoceptive ability is widely described in people suffering from anxiety disorders (Domschke et al 2010;Garfinkel and Critchley 2013;Khalsa et al 2018;Pang et al 2019;Quadt et al 2018) relationships between interoceptive accuracy and anxiety score are frequently described in 'analogue' populations (e.g. Dunn et al, 2010).…”
Section: Discussionmentioning
confidence: 99%